1998
DOI: 10.1152/jn.1998.80.3.1236
|View full text |Cite
|
Sign up to set email alerts
|

Serum From Diabetic BB/W Rats Enhances Calcium Currents in Primary Sensory Neurons

Abstract: We examined the hypothesis that exposure of nondiabetic rat dorsal root ganglion (DRG) neurons to sera from diabetic BB/W rats would produce an increase in calcium currents associated with impaired regulation of the inhibitory G protein-calcium channel complex. Acutely dissociated rat DRGs were incubated for 18-24 h in medium supplemented with sera (10% vol/vol) from either diabetic rats with neuropathy or age-matched, nondiabetic controls. Exposure of DRG neurons to sera from diabetic BB/W rats resulted in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…and Ca V 1.3 -/-b cells. This is in line with previous findings from our group and others [19,[42][43][44][45]. More importantly, we are able to mechanistically interpret T1D serum-induced hyperactivation of b cell Ca V 1 channels by thoroughly examining the biophysical properties of single Ca V 1 channels in Ca V 1.…”
Section: Discussionsupporting
confidence: 91%
“…and Ca V 1.3 -/-b cells. This is in line with previous findings from our group and others [19,[42][43][44][45]. More importantly, we are able to mechanistically interpret T1D serum-induced hyperactivation of b cell Ca V 1 channels by thoroughly examining the biophysical properties of single Ca V 1 channels in Ca V 1.…”
Section: Discussionsupporting
confidence: 91%
“…The experiments showing increased labeling of autophagosomes with anti-LC3 immunoreactivity in DRG neurons of streptozotocindiabetic rats follow our earlier observations highlighting a potential role for autoimmunity in the induction of cellular stress 6 and apoptosis in diabetic neuropathy. 5 Those observations are extended in the present report by the experiments conducted with SH-SY5Y cells, exposed to normal or diabetic neuropathic sera, in media containing similar concentrations of glucose and other nutrients.…”
Section: Discussionsupporting
confidence: 87%
“…1 In addition to metabolic and endocrine abnormalities, recent studies support the presence of autoimmune immunoglobulin in the sera of patients with type 1 and type 2 diabetes that induce apoptosis in cultured neurons. [2][3][4] These autoimmune antibodies are present in complement-inactivated sera from humans 5 and rat models 6 and suggest a role for autoantibodies in the pathophysiology of diabetic neuropathy. It is noteworthy that the level of apoptosis observed in primary afferent nerves in situ (~1-4%) is consistent with the modest loss in neurons reported in peripheral nerve tissues in diabetes, [7][8][9] making it difficult to account for the more robust deficits in peripheral nerve function, e.g., slowing in nerve conduction velocity, altered sensation and autonomic nervous system dysfunction observed concurrently with apoptosis.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…These rats, after 8 months of diabetes, also upregulate T-type channels in small DRG cells (Hall et al, 1995). Serum from BB/W rats increases both HVA and T-type currents in DRG cells grown in culture without alterations in T-type channel inactivation kinetics (Ristic et al, 1998). In contrast, we found that T-type channels in medium-size neurons in STZ-induced diabetic neuropathy show prominent changes in voltage-dependent inactivation, allowing a greater fraction of the channels to be available for activation during both short and prolonged periods of depolarization.…”
Section: Functional Implicationsmentioning
confidence: 92%